(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Under the same condition, a series of the catalysts of Ni-Fe system with different metal ratio (100–65 mass. % of Ni — 0–35 mass. % of Fe) were prepared by coprecipitation method with NH4OH as a precipitation agent. All samples were reduced by He+H2 mixture from oxide form to the metal state and then they were used in methane production from CO2 and H2. The optimal temperature (300°C) of Ni-Fe oxides reduction to metal condition was determined by TGA method. Based on the experimental data on loss of mass, activation energy (Ea) of samples’ reduction for Ni80Fe20 and Ni75Fe25 was estimated. The explanation of such a significant difference in activation energy rates is the formation of intermetall FeNi3 in the range of 72–77 mass % of Ni, as well as that the reduction activation energy of a particular substance is lower then in solid solution of γ+FeNi3 within the concentration range of 60–70 mass. % and 80–100 mass. % of Ni. Investigation of catalytic activity of Ni-Fe systems in the reaction of CO2 hydrogenation was performed. Among the tested samples, Ni80Fe20 catalyst with the most specific surface area showed the best performance at 300–500°С, and the methane yield amounted to 62%. Ni75Fe25 sample with smallest specific surface area showed the worst catalytic performance in term of conversion of CO2 and yield for CH4. The correlation between samples’ phase composition and their catalytic activity was estimated.